Predictors of persisting psychotic like experiences in children and adolescents: a scoping review - Kálmán, János L.; Bresnahan, Michaeline; Schulze, Thomas G.; Susser, Ezra S. (Schizophrenia research, 2019)
Background - Subclinical psychotic experiences (PLEs) are among the frequently reported mental health problems in children/adolescents. PLEs identified in cross sectional studies of children/adolescents are associated with current and future mental health problems. These associations are stronger for PLEs that persist over time. Hence, it could be useful to examine which children/adolescents with PLEs at a first assessment (baseline) are more likely to have PLEs at subsequent assessments. - Methods - We conducted a scoping review of studies that examined whether characteristics of children/adolescents (≤18years) with PLEs at baseline predict whether PLEs are likely to be persistent or remittent at subsequent assessments. We included studies published between January 2002 and December 2017, conducted on general child/adolescent populations of ≥300 individuals, that provided data on PLEs for at least 2 time points, had available follow-up data for ≥50% of those assessed for PLEs at baseline and targeted for follow-up examination, and reported the differences between individuals with PLEs that persisted or remitted during the study period. - Results - Six studies met our criteria. Each of them investigated a wide range of baseline characteristics but no predictor of persistence was replicated. - Conclusions - Our knowledge about which children/adolescents with PLEs at an initial assessment are likely to have persistent PLEs at subsequent assessments is sparse. A handful of predictors of persistent PLEs have been investigated so far, and none replicated. A better understanding of these predictors would be an important complement to investigations examining the evolution of PLEs and of mental health problems in children/adolescents.
Gesehen am 06.12.2019
Received 4 October 2018